ALGUNAS REFLEXIONES SOBRE LA PARTICIPACION VECINAL EN EL GOBIERNO DE LAS CIUDADES DE LA CORONA DE ARAGON (ss. XII-XV) - Narbona Vizcaíno, Rafael (Res Publica. Revista de Historia de las Ideas Políticas, 2023)
A comparative and critical analysis is made of the various modes of participation in the high and late medieval urban governments under the Crown of Aragon. In the process, the traditional thesis of the citizensÆ participation (along the lines of a communal democracy) is set against the self-propagation of patrician power (typically oligarchic practices), and at the same time the ultimate direction of the institutional developments is examined. In order to do this, and as an exercise in comparative history between the various fueros, attention is paid firstly to the origins of the municipality, which has to be understood in relation to the evolution of its institutions, its forms of political organisation and its very relationship with the monarchy.
Keywords: Municipal power; Crown of Aragon; Citizens; representation; Patriciate; Institutions